2012
DOI: 10.1345/aph.1m721
|View full text |Cite
|
Sign up to set email alerts
|

Lurasidone: An Atypical Antipsychotic for Schizophrenia

Abstract: Lurasidone has shown efficacy when compared to placebo in acute schizophrenia. Full characterization of the adverse effect profile and cognitive and affective benefits requires publication of trials with longer durations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The T1/2 was found somewhat different in patients with schizophrenia (range 28.8 --37.4 h) after a single dose (120 --160 mg/day) from healthy volunteers (range 12.2 --18.3 h) and after a single-dose administration of 100 mg or less [13].…”
Section: Pharmacokinetics/pharmacodynamics Proprieties Of Lurasidonementioning
confidence: 79%
See 2 more Smart Citations
“…The T1/2 was found somewhat different in patients with schizophrenia (range 28.8 --37.4 h) after a single dose (120 --160 mg/day) from healthy volunteers (range 12.2 --18.3 h) and after a single-dose administration of 100 mg or less [13].…”
Section: Pharmacokinetics/pharmacodynamics Proprieties Of Lurasidonementioning
confidence: 79%
“…It was indicated as causal of a reduction of neurotrophin expression in the pre-frontal cortex of psychotic states, but lurasidone chronic high dosage treatment normalizes this reduction [61]. Such evidence suggests that epigenetic-related mechanisms may have a relevant role in the long-term activity of anti-psychotic actions of lurasidone [13].…”
Section: Development Of Clinical Studies On Lurasidonementioning
confidence: 99%
See 1 more Smart Citation
“…Lurasidone also has partial agonistic properties of high affinity at the 5-HT 1A receptor 24. Lurasidone has much greater binding affinity at the 5-HT 7 receptor compared to other second-generation antipsychotics, and the blockade of this receptor subtype is also thought to contribute to lurasidone’s antipsychotic actions 24,26. There have also been several studies that suggested the positive impacts of 5-HT 7 antagonistic effects on memory27 and affective symptoms 28.…”
Section: Review Of the Pharmacology Mode Of Action And Pharmacokinementioning
confidence: 99%
“…They also have high binding affinity at 5-HA 1A and 5-HT 7 , which is comparable to lurasidone. Both metabolites, especially ID-14283, seem to contribute to the antipsychotic action of lurasidone 24,26. The T max of ID-14283 is 1.6 hours to 1.8 hours, and its half-life (T 1/2 ) is 7.48–10 hours 26,31…”
Section: Review Of the Pharmacology Mode Of Action And Pharmacokinementioning
confidence: 99%